MODERATISM OF PESANTREN EDUCATION IN INDONESIA - Dwi Kusmira (Pondok Pesantren Modern Islam Assalaam, 2018)
ASEAN Economic Community (MEA) as an economic integration of ASEAN will have an impact on various sectors of life including education system in Indonesia. As there is no exception to pesantren education. The problem that arises is how pesantren is known as an indigenous education that is able to adapt to the global competition of MEA and how the pesantren redesigns the concept of moderate education so as to strengthen the competitiveness of boarding schools without having to lose the identity of a pesantren as an indigenous education in Indonesia. The results of the study have indicated that pesantren is based on some moderate values existing in the pesantren world is ready to enter the ASEAN Economic Community. Some moderate values for dealing with MEAs are; multicultural values as adaptative concepts of the times, in-dichotomic academic traditions. modern management based on quality and collective leadership collegial and also pesantren as the economic axis of the ummah.